Comparison of the Strategic Plans of the Ministry of Education and Culture and Universitas Brawijaya Based on Theoretical - Lestari Eko Wahyudi; Abela Chairunissa; Eva Fadilah Ramadhani; Durratun Nashihah; Muhammad Naufal Luthfi (Journal Governance Society, 2024)
Education has a crucial role in determining the direction of a nation's development. Indonesia's Gross Enrollment Rate (APK) data shows a positive trend, but challenges in the quality of education remain, especially in terms of literacy, numeracy and understanding of science based on PISA scores. The inequality of educational attainment between regions indicates the need to increase access and quality of education evenly throughout Indonesia. Inadequate curriculum in developing basic competencies is one of the main causes of suboptimal achievements. Apart from that, Indonesia also faces the challenge of low public IQ levels, showing the importance of improving the education system to increase the nation's overall competitiveness. The process of preparing the vision, mission and strategic objectives by the Ministry of Education and Culture and Brawijaya University adopts an approach that is in accordance with theory, but the main challenge lies in implementing the strategic plan. Brawijaya University demonstrated excellence in overcoming implementation barriers, which enabled them to achieve strategic goals more effectively. In this context, alignment between vision, mission and goals is key in designing and implementing sustainable strategic